Ortholinea nupchi n. sp. (Myxosporea: Ortholineidae) from the urinary bladder of the cultured olive flounder Paralichthys olivaceus, South Korea. (June 2023) - Shin, Sang Phil; Jin, Chang Nam; Sohn, Hanchang; Kim, Jeongeun; Lee, Jehee
Abstract: A new myxosporean parasite, Ortholinea nupchi n. sp. (Myxozoa; Bivalvulida), was isolated from the urinary bladder of the olive flounder Paralichthys olivaceus cultured on Jeju Island, Korea. Mature spores were subspherical in the valvular and apical views and ellipsoidal in the sutural view. The spores measured 7.6 ± 0.5 μm in length, 6.7 ± 0.3 μm in thickness, and 7.3 ± 0.5 μm in width. Two pyriform polar capsules measured 3.2 ± 0.1 μm in length and 2.7 ± 0.1 μm in width and were located at the same level at the anterior half of the myxospores. The suture line was straight in the middle of the spores, and the surface ridges ranged between five and seven, forming an intricate pattern. The result of the 18S rDNA comparison showed ≤ 93.0% similarity with other Ortholinea species. The phylogenetic tree demonstrated that O. nupchi n. sp. was closest to O. auratae and clustered with oligochaete-infecting myxosporeans (OIM) having urinary system infection tropism. Based on the comparison of environmental and host factors in the phylogenetic groups of the OIM clade, we propose that the infection of O. nupchi n. sp. originated from marine oligochaetes. Graphical abstract: Unlabelled Image Highlights: A novel Ortholinea species was described from urinary bladder of Paralichthys olivaceus. Morphological and phylogenetic analyses were performed. A new species was denominated Ortholinea nupchi n. sp. The phylogeny suggested the infection of O. nupchi originated from marine oligochaetes.